The Effect of Accounting Conservatism on Investment Efficiency (An Empirical Study on Insurance Companies Listed in Damascus Exchange Securities) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study tested the impact of accounting conservatism on corporate investment efficiency, while distinguishing between over and under investment which indicate inefficiency of investment. to achieve that goal; secondary data was collected from the annual financial reports of the insurance companies listed on the Damascus Exchange Securities, which are available on the official website of that market. The number of companies reached 6 insurance companies, and the study covered an 11-year period from 2010 to 2020, with a total of 66 observations. Data was analyzed using E-views 10. The results showed that accounting conservatism has a positive effect on over-investment, this result indicates that accounting conservatism has increased the managers motivation to accept investment projects with negative net present value, while its effect on under-investment was negative, this result indicates that the conservatism has Improved investment efficiency, and encourage companies not to lose investments with positive net present value.